Faktor Yang Berhubungan Dengan Kelelahan Kerja Pada Dosen Fakultas X Universitas X Tahun 2022 - Marisa Novianti; Ruwiah; Syawal Kamiluddin S (Formosa Journal of Sustainable Research, 2022)
This study aims to determine the relationship between working time, workload and work stress on work fatigue in the lecturers of Faculty X, University of X. The type of research carried out is observational analytic with a cross sectional study approach with primary and secondary data collection methods. The sample in this study was active lecturers at the Faculty of X, University of X, totaling 35 people who were taken using purposive sampling technique. Data collection by using a questionnaire. The results showed that there was no relationship between work time and work fatigue (p=1,000), there was a relationship between workload and work fatigue (p=0.018), and there was a relationship between work stress and work fatigue (p=0.005). Lecturers should always pay attention to work time, rest time and time management and reduce excessive workload so that teaching time does not collide with each other which can cause work fatigue.